1997
DOI: 10.1177/026921559701100111
|View full text |Cite
|
Sign up to set email alerts
|

Aspiration following stroke: is it related to the side of the stroke?

Abstract: Continuing aspiration may be related to the side of the cerebral lesion.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
30
1
2

Year Published

1999
1999
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(37 citation statements)
references
References 9 publications
4
30
1
2
Order By: Relevance
“…It was observed that a significant increase in the activation of the sensorimotor cortex occurs on the left compared to the right during swallowing (8) . However, most studies report that patients with lesions in the right hemisphere have more swallowing dysfunction (44) . It was described that lesions located in the right hemisphere cause more pharyngeal changes and that lesions in the left hemisphere cause more changes in the oral phase of swallowing (16) .…”
Section: Discussionmentioning
confidence: 99%
“…It was observed that a significant increase in the activation of the sensorimotor cortex occurs on the left compared to the right during swallowing (8) . However, most studies report that patients with lesions in the right hemisphere have more swallowing dysfunction (44) . It was described that lesions located in the right hemisphere cause more pharyngeal changes and that lesions in the left hemisphere cause more changes in the oral phase of swallowing (16) .…”
Section: Discussionmentioning
confidence: 99%
“…Smithard et al found that patients with RHD were more likely to have persistent dysphagia than patients with LHD [19]. When evaluated acutely, four patients with RHD and nine patients with LHD had aspirated (N = 87); however, at 1 month, seven patients with RHD and no patients with LHD had aspirated.…”
Section: Introductionmentioning
confidence: 99%
“…However, there is an increasing need to improve the accuracy of diagnostic tests, due to challenges including difficulties in evaluating dysfunction (for example, doctors cannot execute the sophageal television lens examination for patients with severe stroke) [5]. Figure 1 shows the anatomical structures of dysphagia, and Table 1 shows the 18 diagnosis items of the water swallow test scale proposed by DG Smithard et al at the South University of Manchester Hospital [2,[6][7][8][9].…”
Section: Introductionmentioning
confidence: 99%